Comparison of the effects of cooking methods on nutritional composition of fresh and salted Tenualosa ilisha - Sanchari Goswami; Kuntal Manna (Aquaculture and Fisheries, 2020)
Fresh and salted Tenualosa ilisha is very popular among the common people of Tripura, North-eastern part of India. In the present study, nutritional value of fresh and salted T. ilisha and the effects of different cooking methods such as boiling and frying on them were evaluated. Significant differences were detected in proximate composition as well as in mineral, amino acid and fatty acid content. The increased amount of protein, ash, dry matter and mineral content was observed in salted T. ilisha but reverse was observed in case of amino acid and fatty acid content. Fried sample of both fresh and salted T. ilisha contained more amount of protein, fat, dry matter, ash, minerals and fatty acids than the boiled fish which play an important role in human health. In conclusion, frying process for preparation of fish is found to be good for cooking.